2011
DOI: 10.1007/s00726-011-1156-z
|View full text |Cite
|
Sign up to set email alerts
|

The suppression of thymic stromal lymphopoietin expression by selenium

Abstract: Thymic stromal lymphopoietin (TSLP) is a key mediator of allergic diseases such as allergic rhinitis, asthma, and atopic dermatitis. Selenium (Se) has various effects such as antioxidant, antitumor, antiulcer, and anti-inflammatory effects. However, the effect of Se on the production of TSLP has not been clarified. Thus, we investigated how Se inhibits the production of TSLP in the human mast cell line, HMC-1 cells. Se suppressed the production and mRNA expression of TSLP in HMC-1 cells. The maximal inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…IL-1β-converting enzyme (ICE), known as caspase-1, is a protease in converting inactive IL-1β to active [42], and is known to inhibit activation of apoptosis [43]. Selenium recently was reported capable of inhibiting caspase-1 activation [44], so as to suppress tumor angiogenesis [45]. We found that the treatment of selenium yeast truly can neutralize expression of IL-1β (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…IL-1β-converting enzyme (ICE), known as caspase-1, is a protease in converting inactive IL-1β to active [42], and is known to inhibit activation of apoptosis [43]. Selenium recently was reported capable of inhibiting caspase-1 activation [44], so as to suppress tumor angiogenesis [45]. We found that the treatment of selenium yeast truly can neutralize expression of IL-1β (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Western blot analysis. The supernatants of the homogenized liver tissues were prepared in a sample buffer [62.5 mM Tris hydrochloride (Tris-HCl), pH 6.8, 2% sodium dodecyl sulphate (SDS), 20% glycerol and 10% 2-mercaptoethanol], as previously described (28)(29)(30). The samples were heated at 95˚C for 5 min and briefly cooled on ice.…”
Section: Quantitative Polymerase Chain Reaction (Qpcr)mentioning
confidence: 99%
“…Total RNA was isolated from liver tissues using an easy‐BLUE™ RNA extraction kit (iNtRON Biotech, Republic of Korea) and quantitative real‐time PCR was performed using a SYBR Green master mix. mRNA was analyzed using an ABI StepOne real‐time PCR System (Applied Biosystems, Foster City, CA), as previously described .…”
Section: Methodsmentioning
confidence: 99%